2013
DOI: 10.1097/mnm.0b013e32835c0964
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of multislice SPECT/CT in impingement syndrome and soft-tissue pathology of the ankle and foot

Abstract: Tc-99m methylene diphosphonate bone SPECT/CT is useful in localizing and characterizing impingement syndrome and soft-tissue pathology in patients with ankle/foot pain. SPECT/CT may complement MRI and ultrasonography in the investigation of impingement syndrome and soft-tissue pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 10 publications
0
27
0
5
Order By: Relevance
“…[7810] In a small group of 25 patients, Mohan et al . found that the SPECT/CT study provided additional information compared to planar scintigraphy in 20/25 (80%) patients, with more accurate pathology localization in 16/25 (64%) and new abnormalities in 10/25 (40%) patients.…”
Section: Added Value Of Single-photon Emission Computed Tomography/comentioning
confidence: 99%
See 3 more Smart Citations
“…[7810] In a small group of 25 patients, Mohan et al . found that the SPECT/CT study provided additional information compared to planar scintigraphy in 20/25 (80%) patients, with more accurate pathology localization in 16/25 (64%) and new abnormalities in 10/25 (40%) patients.…”
Section: Added Value Of Single-photon Emission Computed Tomography/comentioning
confidence: 99%
“…[8] In a cohort of patients with impingement syndromes and soft-tissue pathology, improvement in localization and characterization of uptake with SPECT/CT was reported in 76% (31/43) patients when compared to clinical assessment and conventional two-phase bone scan. [10]…”
Section: Added Value Of Single-photon Emission Computed Tomography/comentioning
confidence: 99%
See 2 more Smart Citations
“…The accuracy, sensitivity, specificity, and positive and negative predictive values of SPECT/CT in this series was 94 %, 95 %, 83 %, 98 % and 71 %, respectively. Chicklore et al found that SPECT/CT was useful for the evaluation of impingement syndromes and soft-tissue pathologies [48]. SPECT/CT can be used for the postoperative evaluation of the foot after arthrodesis to assess nonunion or the development of osteoarthritis in adjacent joints due to mechanical overload.…”
Section: Footmentioning
confidence: 99%